Education promotion based on "mobile technology" in the Critical Care Nursing Department: Four-phase intervention - Somayeh Ghafari; Ahmadreza Yazdannik; Shahla Mohamadirizi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Evaluation of students' clinical performance is an essential part of nursing education. Mobile technology is one of the new methods of evaluation that has opened a new horizon for nursing professors. Therefore, this study aimed to design, implement, and evaluate mobile health technology in critical care nursing department in four-phase intervention. METHODS: This study was a four-stage educational intervention in which all postgraduate students of intensive care nursing in Isfahan University of Medical Sciences participated in the study. The four steps were designing and developing a logbook, needs assessment, designing and implementing an Android app, and evaluating users (students) of the Android app. Subjects' satisfaction scores were collected using a researcher-made questionnaire with 14 questions. Data were analyzed using SPSS 14 software. RESULTS: In this study, a clinical practice evaluation app was designed at four levels of access (student, professor, department manager, and faculty dean). The results showed that more than half of app users reported this technology in terms of an overall response to the tool (87.5%), tool specificity (100%), the amount of information displayed (75%), page layout (62.5%), information rate (75%), recall information (87.5%), and ease of doing instructions (100%) were positive. CONCLUSION: Evaluation of clinical practice using technology was associated with increasing students' satisfaction with evaluation method. In addition, this application enabled the simultaneous interaction between the professor with the higher and lower ranks, including the department manager and student and vice versa and the simultaneous recording of this interaction.